Stochastic inventory control model with two stages in ordering process - Kopytov, Eugene; Greenglaz, Leonid; Tissen, Fedor (Journal of Business Economics and Management, 2006)
The purpose of offered work is the construction of a stochastic single‐product inventory control model for the chain “producer – wholesaler – customer”. Given situation takes place in many transport and industrial companies. Criterion of optimization is minimum of average expenses for goods holding, ordering and losses from deficit per a time unit.First published online: 14 Oct 2010